Exploring ESL learners' reading test taking strategies - Charanjit Kaur Swaran Singh; Eng Tek Ong; Tarsame Singh Masa Singh; Mahendaran Maniam; Tunku Mohani Tunku Mohtar (Studies in English Language and Education, 2021)
This study examined the test taking strategies of weak ESL students of an English language proficiency course. Test taking strategies are known as the methods that test takers use as an alternative aimed at attaining correct answers on a specified form of language assessment. The study adopted a qualitative study. The participants in this study were forty-four learners from the Bachelor of Arts Program. The learners were asked to think aloud while reading an assigned text to answer the questions. Four learners’ thinking aloud recordings were transcribed and analysed. Focus group interviews were carried out for triangulation purposes. Data collected were analysed manually. The ESL learners implemented many test taking strategies as they coped with the reading comprehension test. The findings of the study show how ESL students used cognitive, metacognitive, compensating, and social strategies. Participants expressed that understanding and reading the passage allowed them to draw conclusions better in answering the multiple choice questions. The findings revealed that they used a compensation strategy whereby they tried guessing the answers on a number of occasions. The findings of the study implicate teachers’ roles in L2 reading and also to guide the ESL learners in the process of answering reading passage and answer the comprehension questions.